"Would You Allow Your Wife to Dress in a Miniskirt to the Party"?: Batterers Do Not Activate Default Mode Network During Moral Decisions About Intimate Partner Violence. Issue 3 (February 2022) - Marín-Morales, Agar; Bueso-Izquierdo, Natalia; Hidalgo-Ruzzante, Natalia; Pérez-García, Miguel; Catena-Martínez, Andrés; Verdejo-Román, Juan
Moral convictions consist of assessments based on perceptions of morality and immorality, of right and wrong. There are people who, based on morality, commit crimes. For instance, social and moral norms based on inequality appear to play an important role in the batterer's behavior to commit violent acts. Research shows that batterers consider themselves to be moral persons, are defenders of their beliefs, and, if necessary, are self-delusional, enjoying a "feeling" of moral worth. The main aim of this work was to uncover the brain mechanisms underlying moral decision making related to intimate partner violence (IPV) against women. We conducted a functional magnetic resonance imaging (fMRI) study comparing moral decisions related to IPV and general violence (GV) in a sample of convicted Spanish men. The two groups of our sample were recruited from the Center for Social Insertion (CSI; Granada, Spain): batterers (BG, n = 21), people convicted for IPV, and other criminals (OCG, n = 20) convicted of violating other legal norms without violence against people. Greene's classical dilemmas were used to validate IPV and GV dilemmas. First, our results showed that IPV and GV dilemmas activate the same brain areas as those activated by Greene's dilemmas, primarily involving the default mode network (DMN), which suggests that IPV and GV dilemmas are both moral dilemmas. Second, our results showed that other criminals activated the DMN during both types of dilemmas. Nevertheless, batterers activated the DMN during the GV dilemmas but not during the IPV ones, suggesting that decisions about their female partners do not entail moral conflict. Thus, these preliminary results showed that batterers do not activate moral areas during IPV dilemmas specifically, but do so during GV dilemmas. These results suggest that intervention programs for batterers should aim to specifically modify the value system held by the abuser toward his female partner and not toward other people.